BARAAN: ISLAMIC PHILOSOPHY THROUGH RELIGIOUS TRADITION OF EID-FITR IN BENGKALIS RIAU - Suroyo, Suroyo; Fredyarini Soedjiwo, Novena Ade; Putra, Bima Maulana; Soriente, Antonia (IAIN Palangka Raya, 2023)
This research explores the Islamic philosophy embedded in the cultural traditions of the Bengkalis people. The research was motivated by the need to understand the unique Islamic perspective of the Bengkalis people and how it affects their way of life. The research methodology used in this study is qualitative, with the data collection process conducted through observation, interviews, and document analysis. The participants in this study were members of the Bengkalis community and the data analysis process involved identifying key themes and patterns that emerged from the data collected. The study found that the cultural traditions of the Bengkalis community are deeply rooted in Islamic philosophy, which is reflected in their daily practices, beliefs and values. The community's strong adherence to Islamic principles has helped shape their way of life, as well as their social and economic structure. So the findings of this research are